Research of the Vibration Characteristic of Automotive Drive Shaft in the Transmission - Kong Huchen (Jixie chuandong)
Aiming at the automotive drive shaft in the transmission existing inevitably resonance phenomenon during the high- speed operation,the drive shaft is regarded as research object,the vibration modal analysis is carried out and the natural frequency and modal vibration mode are got. The results show that the drive shaft of the finite element simulation results and experimental results are identical with each other,the resonance frequency with 50 Hz power frequency and the frequency of the motor vehicle doesn’t occur in the process of running,the foundation for fault diagnosis of drive shaft,comfort and smoothness of the automobile are provided.